2021
DOI: 10.3390/molecules26185661
|View full text |Cite
|
Sign up to set email alerts
|

Local Oral Delivery Agents with Anti-Biofilm Properties for the Treatment of Periodontitis and Peri-Implantitis. A Narrative Review

Abstract: Despite many discoveries over the past 20 years regarding the etiopathogenesis of periodontal and peri-implant diseases, as well as significant advances in our understanding of microbial biofilms, the incidence of these pathologies continues to rise. For this reason, it was clear that other strategies were needed to eliminate biofilms. In this review, the literature database was searched for studies on locally delivered synthetic agents that exhibit anti-biofilm properties and their potential use in the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 109 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…Among them, quercetin (QUE), a flavonoid compound ubiquitously present in roots and leaves of various vegetables, has a plethora of beneficial effects on human health, including in preventing and treating various systemic and oral diseases [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, quercetin (QUE), a flavonoid compound ubiquitously present in roots and leaves of various vegetables, has a plethora of beneficial effects on human health, including in preventing and treating various systemic and oral diseases [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Th), infiltration of inflammatory cells, and optical density of IL-1, TNF-α, and TGF-β. Another study developed a chitosan/cyclodextrin drug delivery system loaded with minocycline, which can inhibit the biofilm formation of Streptococcus gordonii and P. gingivalis (Elnagdy et al, 2021;Li et al, 2021). The developed drug delivery system alleviated several histological changes, including GI, TM, the distance between CEG and ABC, proliferation and erosion of periodontal epithelial cells, and bone resorption.…”
Section: Trend Analysis Of Marine Bioactive Substances (Mbs) Against ...mentioning
confidence: 99%
“…The previous studies have demonstrated that the resistance of bacteria to antibiotics after forming biofilms is 1000 times higher than that in the floating state, which also increases the persistence and recurrence of bacterial infection [ 1 , 2 ]. Biofilms can cause many diseases, such as periodontitis [ 3 ], otitis media [ 4 , 5 ], osteomyelitis [ 6 , 7 ]. Furthermore, it should be noted that biofilms have the capability to adhere to various materials, including catheters [ 8 , 9 , 10 ], prosthetic joints [ 7 , 11 ], contact lenses [ 12 ], mechanical artificial heart valves [ 13 ], and others.…”
Section: Introductionmentioning
confidence: 99%